2014
DOI: 10.1038/ncomms4874
|View full text |Cite
|
Sign up to set email alerts
|

Global warming favours light-coloured insects in Europe

Abstract: Associations between biological traits of animals and climate are well documented by physiological and local-scale studies. However, whether an ecophysiological phenomenon can affect large-scale biogeographical patterns of insects is largely unknown. Insects absorb energy from the sun to become mobile, and their colouration varies depending on the prevailing climate where they live. Here we show, using data of 473 European butterfly and dragonfly species, that dark-coloured insect species are favoured in coole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
203
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(244 citation statements)
references
References 70 publications
21
203
0
1
Order By: Relevance
“…Our data support the MDH and the PPH, but not the TMH, as potential mechanisms driving this pattern in cuticle colour. Although patterns of colour in ectotherms have been extensively researched at the macroclimatic scale, across latitudes and elevations (Bishop et al, ; Zeuss et al, ), studies at the microclimatic scale are scarce (Chown & Gaston, ). Macroclimate is not always a good reflection of the habitat that an organism actually experiences (Kaspari et al, ; Stark et al, ), and there are growing calls to incorporate microclimatic data into analyses of trait–environment relationships and species distribution modelling (Chown & Gaston, ; Kaspari et al, ; Pincebourde & Casas, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the MDH and the PPH, but not the TMH, as potential mechanisms driving this pattern in cuticle colour. Although patterns of colour in ectotherms have been extensively researched at the macroclimatic scale, across latitudes and elevations (Bishop et al, ; Zeuss et al, ), studies at the microclimatic scale are scarce (Chown & Gaston, ). Macroclimate is not always a good reflection of the habitat that an organism actually experiences (Kaspari et al, ; Stark et al, ), and there are growing calls to incorporate microclimatic data into analyses of trait–environment relationships and species distribution modelling (Chown & Gaston, ; Kaspari et al, ; Pincebourde & Casas, ).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of images in field guides for 473 European butterfly and dragonfly species indicated that cooler climates contain darker species and that distribution shifts between 1988 and 2006 resulted in assemblages becoming lighter in regions that warmed [11]. However, whether wing coloration has any thermoregulatory significance was unclear for most species in the analysis [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence for evolutionary changes in body size [3], coloration relative to background matching [4][5][6], and phenology; specifically the timing of diapause [7], of nesting [8] and of flowering [9]. Evidence for evolutionary or historical changes in traits relevant to thermal physiology is limited (but see [10][11][12][13]) Natural history collections offer a largely untapped resource to examine morphological responses to climate change [14]. In particular, insects are abundant in these collections and the thermal significance of morphological traits has been extensively documented for some species.…”
Section: Introductionmentioning
confidence: 99%
“…Being able to heat up and reach optimum body temperatures quickly could increase mobility and minimise predation risk for insects in cool habitats (Lederhouse et al, 1987). Consequently thermoregulatory advantages are frequently proposed to explain organisms exhibiting different luminance patterns along thermal gradients (Zeuss et al, 2014;Bishop et al, 2016;Xing et al, 2016). These advantages could lead to evolutionary adaptations through which individuals found in cooler closed habitats are generally darker, and those found in hotter open habitats are lighter in colour.…”
Section: Introductionmentioning
confidence: 99%